Adjunctive Fluvoxamine for Schizophrenia: A Meta-analysis of Randomized Double-Blind, Placebo-Controlled Trials. Issue 4 (July 2020) - Zheng, Wei; Xiang, Ying-Qiang; Cai, Dong-Bin; Yang, Xin-Hu; Zhang, Ling; Zheng, Wei; Lu, Xiao-Bing; Tong, Yan-Ming; Huang, Xiong; Ungvari, Gabor S.; Sim, Kang; Ning, Yu-Ping; et al.
Abstract: Background: This was a meta-analysis of double-blind, randomized controlled trials that examined the therapeutic effects and tolerability of adjunctive fluvoxamine versus placebo for schizophrenia. Methods: The Review Manager, Version 5.3, was used to analyze data. Results: Five double-blind randomized controlled trials (N = 284) covering 145 patients on adjunctive fluvoxamine and 139 patients on placebo were included in the analyses. Meta-analyses of total psychopathology, and negative, positive, and depressive symptoms did not show significant differences between the fluvoxamine and placebo groups. Two studies examined the effects of adjunctive fluvoxamine on cognitive functioning with mixed findings. Fluvoxamine was superior over placebo in lessening weight gain and metabolic abnormalities. Although fluvoxamine led to more discontinuation, no significant group differences were found regarding adverse drug reactions. Conclusions: There was inconsistent evidence for the therapeutic effect of adjunctive fluvoxamine on cognitive functions and preliminary evidence for alleviating metabolic syndrome caused by clozapine. More studies are needed to explore further the effectiveness of adjunctive fluvoxamine for schizophrenia. Abstract : Supplemental digital content is available in the text.